Enhancing Learning Outcomes of College Students through Smartphone Integration in the Classroom - Gurung, Sandesh Rohit (BARUN Journal, 2024)
The study has been done only based on management faculty students of Barun Multiple Campus in Sankhuwasabha. The limited students have been selected as respondents for this study. The reason is that the area was selected for study because it is accessible for research, and this kind of research has not been done yet in this area. In this paper, one of the smart pillars of using smartphones as learning in college classrooms can benefit students in various ways, such as accessing information, engaging in interactive learning, collaborating on studies, utilizing multimedia resources, learning language, and productivity tools. The study was carried out through a survey and interview with a group of students. The research paper will address the reflections of students with smartphones. And especially, this paper will explore the enhanced learning outcomes of college students through smartphone integration in the classroom to know how the students relate to and enhances their learning.